Purification and Some Properties of Acetic-ester Decomposing Enzymes from Cladosporium cladosporioides No.9 - TAMURA, Gakuzo; AKITA, Osamu; YOSHIZAWA, Kiyoshi; OBATA, Takaji; IWASE, Toshinori; MIURA, Mayumi; HARA, Syodo (Nippon Nōgeikagaku Kaishi, 1990)
Acetic-ester decomposing enzymes (Est I, Est II) were purified from Cladosporium cladosporioides No.9 by column chromatographies on Butyl-Toyopearl 650M and DEAE-Toyopearl 650M, and gel filtration on Toyopearl HW 55. The purified enzymes were homogeneous on polyacrylamide gel electrophoresis. By gel filtration, the molecular weight was estimated to be about 63, 000 for Est I and 66, 000 for Est II. The enzymes were optimally active at 35°C and pH 9.3 for Est I, and at 30°C and pH 9.5 for Est II. Both enzymes were inhibited by diisopropyl fluorophosphate (DFP) and phenylmethanesulfonyl fluoride (PMSF), but were not inhibited by eserine. Therefore it was presumed that these enzymes were carboxyesterases. They hydrolyzed many acetic-esters, but did not hydrolyze triglycerides and monoglycerides. (Received October 16, 1989)